BMS481: Bioanalytical Chemistry / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2022)
The course introduce various scientific instrumentation techniques typically used in biological science analysis. The theory and applications involving the use of chromatography, electrophoresis and various spectroscopy techniques in modern biological laboratories will be discussed.